Effect of milk thistle and silimevit on the functional state and protein synthesizing-function of the liver of laying hens under conditions of cadmium load - Ostapyuk, A. Y.; Остап’юк, А. Й.; Gutyj, B. V.; Гутий, Б. В.; Horalskyi, L. P.; Горальський, Л. П.; Mylostyvyi, Roman; Milostiviy, Roman; Milostivyiy, Roman; Mylostyvyi, R. V.; Mylostyvyi, Roman V.; Mylostyvy, R.; et al. (Львівський національний університет ветеринарної медицини та біотехнологій ім. С. З. Ґжицького, 2023)
The purpose of the work was to study the effect of Cadmium on liver function disorders and to develop practical recommendations for using silimevit and milk thistle to reduce the toxic effect of Cadmium on chickens. To achieve the set goal in experiments on chickens under cadmium load, it was necessary to solve the following tasks: to study the effect of Cadmium on the protein synthesis function of the liver of laying hens; to study the effect of Cadmium on the functional state of the liver of laying hens; to investigate the effect of silimevit and the fruits of milk thistle on the functional state of the liver of laying hens under cadmium load; to investigate the effect of silimevit and milk thistle fruits on the protein synthesis function of the liver of laying hens under cadmium load and to justify the use of silimevit and milk thistle to prevent cadmium toxicosis in chickens. Drinking cadmium sulfate to laying hens violates the liver's functional state and protein-synthesizing function. A decrease in total protein and albumin content in their blood was established (Р < 0.001). An increase in alanine and aspartate aminotransferase activity was detected (Р < 0.001). Silimevit and milk thistle positively affect the functional state of the liver of laying hens under cadmium load, as evidenced by a decrease in the activity of aminotransferases in their blood serum. Silimevit and spotted thistle, under the cadmium load of laying hens, positively affect the liver's protein-synthesizing function, evidenced by an increase in total protein and albumin fraction. Feeding laying hens under cadmium load with slime feed contributed to a better-normalizing effect on the activity of aminotransferases and protein-synthesizing function of the chickens' liver than milk thistle. Метою роботи було вивчити вплив кадмію на порушення функції печінки та розробити практичні рекомендації щодо застосування силімевіту та розторопші плямистої для зниження токсичної дії кадмію на організм курей. Для досягнення поставленої мети в дослідах на курчатах за кадмієвого навантаження необхідно було вирішити наступні задачі: вивчити вплив кадмію на білковосинтетичну функцію печінки курей-несучок; вивчити вплив кадмію на функціональний стан печінки курей-несучок; дослідити вплив силімевіту та плодів розторопші на функціональний стан печінки курей-несучок за навантаження кадмієм; дослідити вплив силімевіту та плодів розторопші плямистої на білково-синтетичну функцію печінки курей-несучок за кадмієвого навантаження та обґрунтувати застосування силімевіту та розторопші плямистої для профілактики кадмієвого токсикозу курчат. Поїння курей-несучок сульфатом кадмію порушує функціональний стан печінки та білсинтезувальну функцію. В їх крові встановлено зниження вмісту загального білка та альбуміну (Р < 0,001). Виявлено підвищення активності аланін- та аспартатамінотрансфераз (Р < 0,001). Силімевіт і розторопша позитивно впливають на функціональний стан печінки курей-несучок при навантаженні кадмієм, про що свідчить зниження активності амінотрансфераз у сироватці крові. Силімевіт і розторопша плямиста при навантаженні курей-несучок кадмієм позитивно впливають на білсинтезуючу функцію печінки, про що свідчить збільшення загального білка і фракції альбуміну. Згодовування курям-несучкам під кадмієвим навантаженням комбікормом зі слизом сприяло кращому нормалізуючому впливу на активність амінотрансфераз і білсинтезуючу функцію печінки курчат, ніж розторопша.
Вплив розторопші та силімевіту на функціональний стан та білсинтезуючу функцію печінки курей-несучок за умов навантаження кадмієм
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: proteins; білки; cadmium; кадмій; toxicology; токсикологія; liver; печінка; laying hens; кури-несучки; aminotransferases; амінотрансферази